Demographic Pattern, Tumor Size and Stage of Breast Cancer in Africa: A Meta-analysis - Olayide, Agodirin; Isiaka, Aremu; Ganiyu, Rahman; Samuel, Olatoke; Halimat, Akande; Julius, Olaogun; Anyan, Romanoff (Asian Pacific Journal of Cancer Care, 2021)
Purpose: Understanding the epidemiology of breast cancer (BC) in Africa, as well as regional variation is essential for planning future intervention. Our objective was to describe summary estimates of socio-demographic and clinical characteristics of BC in Africa, thus providing researchers and policymakers baseline data for planning diagnostic and treatment programs to improve BC outcomes in the future. Method: We screened African publications on BC between 2010 and 2019 in PubMed, AJOL, Google, ScienceDirect, and ResearchGate to estimate the distribution of socio-demographic and clinical tumor characteristics. The meta-analysis used the random effect model. Result: Eighty articles were eligible, including 33,199 total patients. Overall, 58% of patients were <50 years old. In East Africa, 38% (95% CI 31-45) were diagnosed before 40 years. Conversely, in Southern Africa, 37% were diagnosed after 60 years, with Caucasian-like age distribution. The overall prevalence of male BC was high (3%), with East Africa having the highest prevalence (5% (95% CI 5.0-6.0)). Only 2% (95% CI 1-2) of patients were diagnosed with carcinoma-in-situ. Invasive tumors were 7% stage I, 26% stage II, 50% stage III, and 17% stage IV. Seventy per-cent (95% CI 60-80) had clinical nodal involvement. The smallest tumors were in North Africa. The largest and most advanced tumors were in West Africa. Trend analysis showed decreasing age, an increasing population of unmarried BC patients, a relatively high proportion of uneducated BC patients, and a stable proportion of late-stage disease in the last decade. Conclusion: Regional variation in the presentation of BC throughout Africa necessitates region/country-specific targets for improving BC control.